STRATEGI PENGEMBANGAN AGROINDUSTRI MOCAF DI KOTA SINGKAWANG - MARTIYANTI, ANASTASIA ARI; MUANI, ANI; RADIAN, RADIAN (Jurnal Social Economic of Agriculture, 2015)
Mocaf industry in West Kalimantan is located in Singkawang but it is still underdeveloped. Strategic development should be formulated to advance mocaf industry in Singkawang so that  it can achieve its aims and increase the competitiveness in agro-industy. The aims of this research is to identify internal and external factors that influence the development of mocaf agro-industry; and to determine alternative strategies, the best strategy and development strategy priority. This is a descriptive research which  location and number of respondents sample were purposively selected. Data collection used is Delphi Model. Internal and external factors analysis used are IFE Matrix and EFE Matrix. Determination of alternative strategy used is SWOT Analysis. Determination of the strategy priority used is QSPM Matrix. The strength of agro-industry is the excellence of mocaf characteristics. The weakness is the poor management skills of agro-industrialist. The opportunity is the increasing of flour industry. The threat for mocaf agro-industry is the tight competition at cassava industry. The most appropriate strategies are: optimize technology implementation and improve human resource capability. The first priority of development strategy is optimizing the implementation of processing technology to assure product quality. Keywords: strategy, agro-industry, mocaf.